How PT. SINJ Distributes Products Across Indonesia : A Study of Hybrid Distribution Strategies - Zulyani Zulyani; Suharto Suharto; Umar Burhan (Lembaga Pengembangan Kinerja Dosen, 2025)
Distribution inefficiencies remain a persistent challenge for firms operating in geographically dispersed and infrastructure-limited markets such as Indonesia. Companies must navigate logistical complexity while maintaining service reliability and cost-efficiency. This study focuses on PT. SINJ, a major distributor of automotive spare parts headquartered in Gresik Regency, which addresses these challenges through a hybrid distribution strategy. Employing a qualitative descriptive method, data were gathered through interviews, direct observations, and document analysis involving internal managers and regional agents. The findings reveal that PT. SINJ utilizes multiple distribution levels—ranging from direct-to-consumer to agent-based and multi-tier intermediary systems—based on regional infrastructure and accessibility. While this approach enables broad market coverage, it also produces operational constraints, including frequent stockouts, delayed deliveries, and weak coordination between central and field operations. The study recommends actionable improvements, such as implementing real-time inventory tracking across agents, establishing micro-warehouses in underserved regions, integrating automated restocking protocols, and formalizing logistics partnerships with multiple freight carriers. These measures are essential to enhancing PT. SINJ’s distribution resilience, reducing lead time variability, and sustaining competitive advantage in Indonesia’s fragmented logistics landscape.